PENGARUH BUDAYA, SUMBERDAYA MANUSIA, DAN AGAMA TERHADAP KEMISKINAN DI KABUPATEN PIDIE JAYA - Benazir Benazir (Al Mashaadir : Jurnal Ilmu Syariah, 2020)
This research was conducted to determine the effect of culture, human resources and religion on poverty, with a sample of 100 people in Pidie Jaya Regency. Sampling technique using cluster sampling method. Analytical tools used are multiple linear regression and analysis path using SPSS software version 24 for windows. The criteria used in the sample selection are based on statistical data of Pidie Jaya Regency which are grouped into 3 categories, namely agriculture as much as 50 percent, trade and services sector as much as 43 percent, and the rest in the industry 7 percent. This study found that the variables of human and religious resources have a significant effect on poverty, while cultural variables have no significant effect on poverty. Indirectly, cultural variables have a significant effect on poverty that is through the variables of human resources and religious variables. The results of this study indicate that together variables culture, human resources, and religion have a significant effect on poverty in Pidie Jaya regency. Islamic Economics provides solutions to alleviate poverty in Pidie Jaya through hard work, distributing wealth through the distribution of Zakat, infaq and alms and through wakaf and through the improvement of human resources, so that poverty in Pidie Jaya regency must be considered by the government, both local government and government center.